2016
DOI: 10.1037/apl0000040
|View full text |Cite
|
Sign up to set email alerts
|

The lives of others: Third parties’ responses to others’ injustice.

Abstract: This research takes a moral perspective to studying third parties' reactions to injustice as a function of their moral identity. Drawing from theories of deontic justice, moral intuition, moral heuristics, and moral identity, we develop and test a model of the moral underpinnings of third parties' reactions to injustice. First, we compare third parties' responses with interpersonal, distributive, and procedural justice violations. We hypothesize that third parties are more likely to intuit that interpersonal j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 92 publications
4
85
2
Order By: Relevance
“…O'Reilly and Aquino 2011). Turillo et al (2002) found that individuals will punish an unjust coworker, even when the victim is a stranger (for similar findings, see the studies reported by O'Reilly et al 2016). Likewise, managers who are high in moral identity are more likely to punish transgressors than managers low on this measure (Skarlicki and Rupp 2010), though this may depend somewhat on the dimension of moral identity under examination.…”
Section: Overview Of the Three Motives For Justicementioning
confidence: 49%
See 1 more Smart Citation
“…O'Reilly and Aquino 2011). Turillo et al (2002) found that individuals will punish an unjust coworker, even when the victim is a stranger (for similar findings, see the studies reported by O'Reilly et al 2016). Likewise, managers who are high in moral identity are more likely to punish transgressors than managers low on this measure (Skarlicki and Rupp 2010), though this may depend somewhat on the dimension of moral identity under examination.…”
Section: Overview Of the Three Motives For Justicementioning
confidence: 49%
“…As of result of these normative criteria, they adopt a moral duty (deon = duty) to uphold their principles (Folger 2001(Folger , 2011Hannah et al 2014). In this way, justice is valued for its own sake, not simply because of the personal benefits that it may bring to a person (Folger et al 2005; for additional empirical evidence, see O'Reilly et al 2016;Skarlicki and Rupp 2010;Skarlicki et al 2008).…”
Section: Overview Of the Three Motives For Justicementioning
confidence: 99%
“…Our data provides some clues that the social costs of change are potentially very high if we consider that each and every colleague negatively affected by a change process has in turn many colleagues observing her or his pain. From this perspective, the effects of social losses are easily multiplied and extend far beyond any one change recipient to others who may actually not directly lose out because of the change, or may even personally benefit from the change (Skarlicki and Kulik, 2005;O'Reilly et al 2016). These are the types of losses that may be obscured by a focus on change recipients that looks too one-sidedly at personal losses and gains from change processes.…”
Section: Discussionmentioning
confidence: 99%
“…Employees make sense of their organization, by including observations on how external parties (such as customers, community members or the general public) (Dunford et al 2015) and internal parties (e.g. colleagues and superiors) are treated (O'Reilly et al 2016). The moral identity of employees (Aquino et al 2009) can lead people to experience a relatively large circle of moral regard.…”
Section: Broadening the Scope Of Observations Of Change Recipients: Imentioning
confidence: 99%
See 1 more Smart Citation